Bioactive lipids in intervertebral disc degeneration and its therapeutic implications. Issue 10 (11th October 2019) - Das, Undurti N.
Abstract: Intervertebral disc (IVD) degeneration is not uncommon. It is estimated that approximately >60% of individuals above the age of 40 years suffer from IVD degeneration. Shan et al. showed that hyperglycemia can enhance apoptosis of anulus fibrosis cells in a JNK pathway and p38 mitogen-activated protein kinase (MAPK) pathway dependent fashion. Recent studies showed that IVD degeneration could be an inflammatory condition characterized by increased production of matrix metalloproteinases, TNF-α, nitric oxide, IL-6, IL-17, IL-9, and prostaglandin E2, and decreased formation of anti-inflammatory molecules such as lipoxin A4. This imbalance between pro- and anti-inflammatory molecules seem to activate JNK pathway and p38 MAPK pathway to induce apoptosis of anulus fibrosis and nucleus pulposus cells. The activation of production of PGE2 (due to activation of COX-2 pathway) seems to be dependent on p38/c-Fos and JNK/c-Jun activation in an AP-1-dependent manner. These results imply that suppressing pro-inflammatory events in the disc by either augmenting anti-inflammatory events or suppressing production of pro-inflammatory molecules or both may form a logical step in the prevention and management of IVD degeneration.